2018
DOI: 10.2147/jpr.s157957
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between pain outcomes and smoking history following video-assisted thoracic surgery for lobectomy: a retrospective study

Abstract: PurposeThe relationship between chronic smoking history and postoperative pain remains controversial. This study aimed to elucidate this relationship in non-small cell lung cancer (NSCLC) patients who underwent video-assisted thoracic surgery (VATS) lobectomy.Patients and methodsThis retrospective observational study included NSCLC patients treated with VATS lobectomy between January 2011 and July 2017. Demographic and clinical information, including preoperative smoking history, was collected. The primary goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
3
6
0
1
Order By: Relevance
“…Based on previous studies, 1 , 37 smoking is considered to be associated with postoperative HA, which is also confirmed in our study. Both the univariate (OR: 2.61; 95%CI: 1.21–5.64, P =0.013) and multivariate analyses (AOR: 2.32; 95%CI: 0.94–5.72, P =0.069) in our study show that smoking is a risk factor for postoperative HA.…”
Section: Discussionsupporting
confidence: 91%
“…Based on previous studies, 1 , 37 smoking is considered to be associated with postoperative HA, which is also confirmed in our study. Both the univariate (OR: 2.61; 95%CI: 1.21–5.64, P =0.013) and multivariate analyses (AOR: 2.32; 95%CI: 0.94–5.72, P =0.069) in our study show that smoking is a risk factor for postoperative HA.…”
Section: Discussionsupporting
confidence: 91%
“…More smokers underwent VATS compared with non-smokers, and it is therefore important to detect whether the increased risk for postoperative pain was smoking-related actually or if there was other explanations. And in VATS, the association between smoking history and postoperative pain was controversial 25,26 . The multiple analysis of this study indicated that presence of previous history of smoking increased the risk of moderate-severe acute pain following VATS by 86% (OR, 1.86; 95% CI, 1.29 to 2.70, P = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…One cross-sectional study and one small-scale cohort study indicated that smoking cessation after cancer diagnosis reduced pain [ 97 ]. Regarding the relationship between cancer pain and pre- and postoperative smoking, nonsmokers had less opioid consumption in the immediate postoperative period [ 78 , 98 ], while smokers experienced greater chest and wound pain as well as a persistent decrease in physical and social functioning postoperatively [ 99 ]. Since nonsmokers had a higher postoperative quality of life (QOL) [ 99 ], patients undergoing surgery should be smoke-free to minimize the postoperative risks of pain chronification and functional impairments.…”
Section: Clinical Questionsmentioning
confidence: 99%